Solid lipid nanoparticles: a promising tool for insulin delivery. (2nd December 2022) - Mohammadpour, Fatemeh; Kamali, Hossein; Gholami, Leila; McCloskey, Alice P.; Kesharwani, Prashant; Sahebkar, Amirhossein
ABSTRACT: Introduction: Insulin plays a critical role in metabolism modulation including carbohydrate, lipid, and protein metabolism. There is room to improve insulin delivery but optimizing the best carrier remains challenging. Traditional and conventional approaches for insulin delivery do not emulate the normal fate of insulin release in the body. Despite extensive research attempts to overcome this and other challenges, the goal of achieving optimal insulin delivery that emulates the natural system remains unresolved. Areas covered: Solid Lipid Nanoparticles (SLNs) may provide a solution, because they are nontoxic, biocompatible, and straightforward to formulate thus providing a promising platform for achieving targeted and controlled delivery of various therapeutic agents. This review aims to provide an overview on the suitability and application of SLNs for insulin delivery. A special emphasis is placed on the biopharmaceutical aspects of insulin loaded SLNs which have not been explored in detail to date. Expert opinion: SLNs have proven to be safe and versatile drug delivery systems suitable for insulin delivery and capable of improving the efficacy and pharmacokinetic profile of encapsulated insulin. There is still some work to be done to fully explore SLNs' true potential as drug delivery and specifically insulin delivery vehicles suitable for clinical use. ABSTRACT: uf0001